Facilitating student learning: An instructional design perspective for health professions educators - Babu Noushad; Faraz Khurshid (Tabriz University of Medical Sciences, 2019)
Learning in any context involves acquisition, storage and utilization of information by the human memory system. Teaching and learning in health professions is a complex process since it demands learners interact with a number of novel information and concepts and critically analyze them to make important clinical decisions. Therefore, it is imperative for Instructional designers and instructors in health professions education to optimize learning content by considering the characteristics of memory and learning processes of students. This review explores stages of the human memory system, the process of learning, the various types of cognitive loads a learner experiences while learning, and the implications of these factors on instructional designs on the basis of a fairly new theory in educational psychology - the Cognitive Load Theory (CLT). By analyzing the unique features of the processing, storage and retrieval of information by human memory system, this article advocates for health professional educators to plan and design instructional strategies that facilitate student learning.